An Examination of the Perceived Stress and Coping Strategy for Pastorâs Wife in Nigeria - Adesanya, Ibiyinka Olusola (ASPENSI, 2017)
ABSTRACT: The paper examined stress management with special emphasis on Pastorâs wife. This work is germane because of the statistical data in the country of Nigeria which revealed the rate at which people are dying as a result of diseases associated with stress. It is believed that stress, if not properly managed, could lead to several ailments, such as high blood pressure, diabetes, chronic headache, insomnia, and the likes. In addition, the study noted that both male and female are affected by stress, but the fact is that women are more likely to experience stress. This is because she plays multiple roles of a home-maker, a mother, a professional, and the added responsibility of bearing children. The paper further highlights some factors that cause stress for Pastorâs wife. In order to determine this, focal group discussion was used to obtain information and perceptions that might not have come through questionnaire. The findings revealed that overload of work coupled, with the divided attention of their spouse, are the major cause of stress for Pastorâs wife. Also, the empirical data given in the work would serve as convincing grounds for policy makers in both the church and society, at large to work towards educating people to manage their schedule in such a way that it would not take at all on their health. The need for Pastorâs wife to set boundaries for themselves, at least for the purpose of their mental, physical, and spiritual well-being was recommended.Â KEY WORD: Stress; Pastorâs Wife; Coping Strategy; Church and Society; Mental and Physical Health.Â ABSTRAKSI: âSebuah Ujian dalam Menerima dan Strategi Mengatasi Stres bagi Istri Pendeta di Nigeriaâ. Makalah ini meneliti manajemen stres dengan penekanan khusus pada istri Pendeta. Karya ini sangat lekat karena data statistik di negara Nigeria ini mengungkapkan tahapan di mana orang-orang sekarat akibat penyakit yang berhubungan dengan stres. Hal ini diyakini bahwa stres, jika tidak dikelola dengan baik, dapat menyebabkan beberapa penyakit, seperti tekanan darah tinggi, diabetes, sakit kepala kronis, insomnia, dan sejenisnya. Selain itu, penelitian ini mencatat bahwa baik laki-laki maupun perempuan dipengaruhi oleh stres, tetapi kenyataannya perempuan lebih mungkin untuk mengalami stres. Hal ini karena ia memainkan peran ganda dari mengurus rumah tangga, menjadi seorang ibu, pekerja terampil, dan tanggung jawab tambahan bagi sandaran anak-anaknya. Makalah ini lebih menyoroti beberapa faktor yang menyebabkan stres bagi istri Pendeta. Untuk menentukan ini, diskusi kelompok terfokus digunakan dalam memperoleh informasi dan persepsi yang mungkin tidak bisa didapatkan melalui kuesioner. Temuan mengungkapkan bahwa kelebihan beban kerja, ditambah dengan perhatian yang terbagi sebagai pasangan suami-isteri, adalah penyebab utama stres bagi istri Pendeta. Juga, data empiris yang diberikan dalam bekerja untuk melayani merupakan alasan meyakinkan bagi para pembuat kebijakan, baik gereja maupun masyarakat, yang pada umumnya bekerja untuk mendidik umat agar mereka mampu mengelola jadwal sedemikian rupa sehingga tidak akan mengurangi sama sekali kesehatan mereka. Kebutuhan istri Pendeta untuk mengatur batas-batas tugas mereka sendiri, setidaknya untuk tujuan kesehatan mental, fisik, dan spiritual adalah direkomendasikan.KATA KUNCI: Stres; Istri Pendeta; Strategi Mengatasi; Gereja dan Masyarakat; Kesehatan Fisik dan Mental.About the Author: Ibiyinka Olusola Adesanya, Ph.D. is a Lecturer at the Department of Religious Studies ESU (Ekiti State University) in Ado-Ekiti, Nigeria. For academic interest, the author can be contacted via e-mail at: olusolaibiyinka@yahoo.comÂ How to cite this article? Adesanya, Ibiyinka Olusola. (2017). âAn Examination of the Perceived Stress and Coping Strategy for Pastorâs Wife in Nigeriaâ in INSANCITA: Journal of Islamic Studies in Indonesia and Southeast Asia, Vol.2(1), February, pp.43-52. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 2443-1776. Chronicle of the article: Accepted (August 14, 2016); Revised (December 27, 2016); and Published (February 27, 2017).